Artificial intelligence in accelerating vaccine development - current and future perspectives - Kaushik, Rahul; Kant, Ravi; Christodoulides, Myron (Frontiers in Bacteriology, 2023)
Tackling antimicrobial resistance requires the development of new drugs and vaccines. Artificial intelligence (AI) assisted computational approaches offer an alternative to the traditionally empirical drug and vaccine discovery pipelines. In this mini review, we focus on the increasingly important role that AI now plays in the development of vaccines and provide the reader with the methods used to identify candidate vaccine candidates for selected multi-drug resistant bacteria.